KUALITAS FISIK ORGANOLEPTIK LIMBAH TAUGE KACANG HIJAU YANG DIFERMENTASI MENGGUNAKAN Trichoderma harzianum DENGAN LEVEL YANG BERBEDA - Riskha Ayuk Rihadini; S. Mukodiningsih; S. Sumarsih (JURNAL ILMIAH PETERNAKAN TERPADU, 2017)
The objective of this research is to test the physical quality of organoleptic including of the color, smell, texture and pH of fermented bean sprouts using Trichoderma harzianum in different level. This research consists of two phase. The first phase is the process of fermentation of green bean sprouts waste that divided into 4 treatments that is the addition of Trichoderma harzianum at 0%, 2%, 4% and 6% level of 4 replications. The second phase of research is to conduct organoleptic test in covering of the color, smell, texture and pH of fermented bean sprouts waste using Trichoderma harzianum in different level. The material used waste bean sprouts, Trichoderma harzianum, aquades. The data obtained at if statistically using RAL. The result data of the research is tested by F test, if there is effect of treatment then proceed with Duncan test at 5% level. The results showed 2% Trichoderma harzianum giving the best pH 5,18. Trichoderma harzianum 6% gives the best color of  green brown, texture rather crumbs and acid smells. Keywords:Fermented, Bean Sprouts, Organoleptic, Trichoderma harzianum